A conflicted tribe under pressure: A qualitative study of negative workplace behaviour in nursing. (17th November 2022) - Hawkins, Natasha; Jeong, Sarah Yeun‐Sim; Smith, Tony; Sim, Jenny
Abstract: Aim: This study explored workplace interactions of Australian nurses in regional acute care hospitals through an examination of nurses' experiences and perceptions of workplace behaviour. Design: This research is informed by Social Worlds Theory and is the qualitative component of an overarching mixed methods sequential explanatory study. Methods: Between January and March 2019, data were collected from 13 nursing informants from different occupational levels and roles, who engaged in semi‐structured, in‐depth, face‐to‐face interviews. Data analysis was guided by Straussian grounded theory to identify the core category and subcategories. Results: Theoretical saturation occurred after 13 interviews. The core category identified is A conflicted tribe under pressure, which is comprised of five interrelated subcategories: Belonging to the tribe ; ' It's a living hell '; Zero tolerance— ' it's a joke '; Conflicted priorities ; Shifting the cultural norm. Conclusion: This study provides valuable insight into the nursing social world and the organizational constraints in which nurses work. Although the inclination for an individual to exhibit negative behaviours cannot be dismissed, this behaviour can either be facilitated or impeded by organizational influences. Impact: By considering the nurses' experiences of negative workplace behaviour and identifying the symptoms of a struggling system, nurse leaders can work to find and implement strategies to mitigate negative behaviour and create respectful workplace behaviours. Patient or Public Contribution: This study involved registered nurse participants and there was no patient or public contribution. Clinical Trial Registration: Study registration Australian New Zealand Clinical Trials Registry (Registration No. ACTRN12618002007213; December 14, 2018).